PROSPEK PENGOLAHAN MENGKUDU MENJADI SARI MORINDA DI KABUPATEN OKU TIMUR (Studi Kasus Kelompok Pangan Olahan Nay-Nay). - Wardi Saleh (Jurnal Bakti Agribisnis, 2016)
The purpose of this research were to : (1) To know the cost and income of processing mengkudu become morinda juice in Regency OKU East, (2) To know value added of processing mengkudu become sari morinda in Regency OKU East, (3) To know feasibility of processing Mengkudu become morinda juice in Kabpaten OKU East. This research was conducted in Srikaton Village, Buay Madang Timur District, East OKU Regency. This research was conducted in April - May 2015 with the method of case study conducted directly to one farmer who do the making of noni juice in Srikaton Village. This study found that the cost of processing production to morindan mengkuduku morindan in Srikaton Village Buay Madang District East OKU Regency is Rp 351.500 / production process. While the income of Rp 898,500 / production process, the amount of added value obtained from the production value minus the cost between Rp 991.500 / production process and processing mengkudu become morinda juice deserve to be developed dengang NPV criteria present value of home industry juice morinda at an interest rate of 18% Rp 4.715.86 at the highest interest rate ie 36% of Rp -260.924maka value of NPV> 0 feasible business to dilanjutka. The value of Net B / C at the value of NPV that has been discount factor on the home industry business extract of morinda obtained at 1.30 and IRR of 35%.